Bilateral spontaneous dislocation of IOLs within the capsular bag to the anterior chamber in a retinitis pigmentosa patient - Zarnowski, Tomasz; Lekawa-Ilczuk, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
The aim of the paper is to present a case of 82 year old man suffering from retinitis pigmentosa, who over the period of 10 years developed partial, bilateral spontaneous dislocation of IOLs within the capsular bag to the anterior chamber. Material and methods: Complexes of IOLs in the capsular bags with severe capsule contraction were removed and AC IOLs were implanted in both eyes. Results: Vision improved significantly in both eyes. Conclusions: Reported complications can be related to coexisting retinitis pigmentosa in described patient.